Cell-free plasma hemoglobin and male gender are risk factors for AKI in low risk children undergoing cardiopulmonary bypass - Kim-Campbell, Nahmah (Crit Care Med, 2017)
OBJECTIVE: To determine the relationship between the production of cell-free plasma hemoglobin (PHb) and acute kidney injury (AKI) in infants and children undergoing cardiopulmonary bypass (CPB) for cardiac surgery. DESIGN: Prospective observational study SETTING: 12-bed cardiac ICU in a university-affiliated children’s hospital PATIENTS: Children were prospectively enrolled during their pre-operative outpatient appointment with the following criteria: >1month to <18 years old, procedures requiring CPB, no preexisting renal dysfunction. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: Plasma and urine were collected at baseline (in a subset), the beginning and end of CPB, and 2h and 24h after CPB in 60 subjects. Levels of PHb increased during CPB and were associated (p<0.01) with CPB duration (R(2)=0.22), depletion of Hp at end and 24h after CPB (R(2)=0.12 and 0.15, respectively), LDH levels at end CPB (R(2)=0.27), and change in creatinine (R(2)=0.12). 43% of patients developed AKI. There was an association between PHb level and change in creatinine that varied by age (overall [R(2)=0.12, p<0.01], in age >2yrs [R(2)=0.22, p<0.01], and in <2yrs [R(2)=0.03, p=0.42]). Change in PHb and male gender were found to be risk factors for AKI (OR 1.02 and OR 3.78, p<0.05). CONCLUSIONS: Generation of PHb during CPB and male gender are associated with subsequent renal dysfunction in low risk pediatric patients, especially in those >2yrs of age. Further studies are needed to determine whether specific subgroups of pediatric patients undergoing CPB would benefit from potential treatments for hemolysis and PHb-associated renal dysfunction.